Evaluation of postoperative pain in closure versus non-closure of parietal peritoneum at caesarean section - Sharma, Avantika; Hooja, Nupur; Shastri, Apoorv; Dadhich, Brijesh; Manish, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pain is one of the major discomfort which drives post caesarean mothers to seek help. Thus, it is important to know if any change in surgical technique could have effect on the post-operative pain which affects all the woman’s activities. Hence, the study was undertaken to study the effect of closure and non-closure of parietal peritoneum on postoperative pain. Methods: It was a hospital based interventional study done in a tertiary care hospital over one year. Detailed history, investigations, operative details, postoperative outcome in terms of pain were recorded and analysed. Results: Women in the closure group had more postoperative pain. P value was highly significant at 8h (P=0.0001), 16h (P=0.0001), 24h (P=0.00001) and 32h (P=0.000001), 40 hour (P=0.00001) and 48h (P=0.0001). Conclusions: Peritoneal should not be closed routinely in caesarean sections as it is shown to cause less postoperative pain.